2018
DOI: 10.1097/iyc.0000000000000106
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Assessment With Young Children

Abstract: Developmental assessment scales are important tools for determining developmental delays and planning preventive interventions. One broad assessment scale used to evaluate child development is the Battelle Developmental Inventories (BDIs). The BDI-2 has a standardized version in English with good psychometric properties and a translated version in Spanish; however, despite widespread clinical use, there has been limited early childhood development research focused on this assessment tool in the past 10 years. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 34 publications
1
6
0
3
Order By: Relevance
“…We used the Battelle scale 13 to assess children’s development. The instrument has 341 items grouped into five areas: personal/social (capacities and characteristics that allow the child to establish meaningful social interactions), adaptive (capacities and characteristics of the child to be independent and assume personal responsibility for his/her actions), motor (capacities for gross and fine motor control), communication (assesses the reception and expression of information by verbal and nonverbal means) and cognitive (conceptual skills and capacities).…”
Section: The Studymentioning
confidence: 99%
“…We used the Battelle scale 13 to assess children’s development. The instrument has 341 items grouped into five areas: personal/social (capacities and characteristics that allow the child to establish meaningful social interactions), adaptive (capacities and characteristics of the child to be independent and assume personal responsibility for his/her actions), motor (capacities for gross and fine motor control), communication (assesses the reception and expression of information by verbal and nonverbal means) and cognitive (conceptual skills and capacities).…”
Section: The Studymentioning
confidence: 99%
“…Furthermore, the BDI-2 was presented to experts for discussion in professional meetings, as well as by consultation via email. Also, a systematic review of BDI-2 studies and their use in different populations was conducted (Cunha et al, 2018). Finally, the permission to conduct this cross-cultural adaptation study was requested from the Houghton Mifflin Harcourt, the company that holds the intellectual property rights of BDI-2.…”
Section: Stage 1 -Preconditionmentioning
confidence: 99%
“…The Brazilian experts suggested that the conceptual assumptions and the structure (domains) of BDI-2 could be remained for Brazilian children. All of those were analyzed qualitatively considering the results from a systematic review of BDI-2 studies (Cunha et al, 2018). We concluded that the conceptual and methodological assumptions of the BDI-2 are applicable to the cultural context of the Brazilian early childhood population.…”
Section: Stage 1 -Preconditionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies conducted in the United States and China estimate that the prevalence of developmental delays in adolescents is approximately 40% (Cunha, Berkovits, & Albuquerque, 2018;Zhang et al, 2017). This delay can have negative impacts on school performance, increase mortality, reduce professional opportunities, and increase health spending (Quin, 2017;Rios, Santiago, Fernandes, & Alves, 2017;Waite & Creswell, 2014).…”
Section: Introductionmentioning
confidence: 99%